(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
this article analyzes the main principles of using ICT tools in the process of foreign language teaching. To understand the role and importance of ICT in foreign language teaching, to connect the educational requirements and needs of foreign language learners with ICT, to integrate ICT into the educational process, to teach the teacher in the classroom using ICT are discussed. The analysis of current issues in foreign language teaching, such as setting the place, achieving the authenticity of the language and task (exercise), is also included in the article.